Psychometric Properties of the Parental Stress Scale in Swedish Parents of Children with and without Neurodevelopmental Conditions - Lindström Therese; Bergman Tiina Holmberg; Annerstedt Mathilde; Forster Martin; Bölte Sven; Hirvikoski Tatja (Scandinavian Journal of Child and Adolescent Psychiatry and Psychology, 2024)
Parents of children with neurodevelopmental conditions (NDC) are at risk of experiencing elevated levels of parental stress. Access to robust instruments to assess parental stress is important in both clinical and research contexts. Objective: We aimed to evaluate the psychometric properties of a Swedish version of the Parental Stress Scale (PSS), completed by parents of 3- to 17-year-old children, with and without NDCs.